Academic Information System At MA.Fathus Salafi Using The Scrum Method Based On The Laravel Framework - Fathor Rosit; Nur Azizah; Firman Jaya (LPPM Universitas Bhinneka Nusantara, 2026)
In today's digital era, academic data management in schools requires a system that is efficient, secure, and easily accessible. The development of a web-based Academic Information System was carried out to simplify the administration process, recording grades, attendance, lesson schedules, and managing student and teacher data. The development methodology uses a scrum approach that allows an iterative development process and is responsive to user needs. The technologies used include the Laravel version 11 framework and MySQL database, supporting fast, secure, and structured development. System testing was carried out using the black box method which showed that all the main features functioned according to specifications, and could be accessed easily by users. The implementation results show that the system is able to improve the efficiency of academic data management while making it easier for users to input, process data, and report in a real-time and organized manner. The developed system is proven to be able to increase transparency and accountability of administrative processes in schools. The conclusion of this research shows that the application of academic information system based on web technology and scrum methodology is able to produce a reliable, fast, and effective system. It is recommended that school managers continue to utilize, develop, and conduct regular training so that the system remains relevant and able to optimally support academic activities in the futurePrivacy Policy.